A multimodal investigation of a pink-discoloured canine tooth in a jaguar (Panthera onca): a clinical, computed tomographic, microstructural, ultrastructural, and computer-aided design/ computer-aided manufacturing prosthodontic reconstruction study - Nedelea, Raluca Ioana; Gal, Adrian Florin; Rus, Vasile; Marza, Sorin Marian; Tripon, Septimiu; Deak, Georgiana; Borzan, Mihai Marian; Chișamera, Gabriel; Mureșan, Ovidiu; Dumitru, Răzvan Vicențiu; Mătură, Cristinel Cezar; Panaitescu, Paul-Stefan; et al. (Frontiers in Veterinary Science, 2025)
Wild animals in captivity are prone to developing dental diseases. Pink-discoloured canine teeth in jaguars are often seen in wildlife photographs but are rarely reported in the literature, and none have been formally investigated. Within 24 h post-mortem, the oral cavity of a zoo jaguar was investigated using computed tomography (CT). One pink-discoloured canine tooth was atraumatically extracted, fixed, and stained for histological and transmission electron microscopy (TEM) examination. The intravitam pink-discoloured canine tooth exhibited no evidence of periodontal or periapical lesions. Microscopically, the dental pulp revealed numerous ectatic blood vessels with numerous thrombi that occluded the blood vessels. A high percentage of thrombi presented with the retunnelling phenomenon. Fluorescence imaging confirmed the presence of haemoglobin in the dentinal tubules. The study, the first of its type, sheds light on an intravitam pink-discoloured canine tooth opening, a hitherto unexplored topic in zoo dentistry. For the skull to be accepted into the zoological collection of the National Institute of Biology, the extracted canine tooth had to be replaced by a 1:1 scale prosthodontic reconstruction, macroscopically identical to the natural tooth. Prosthodontic reconstruction was performed using computer-aided design and computer-aided manufacturing (CAD/CAM) technology. This study, the first of its kind, investigates an intravitam pink-discoloured canine tooth in a jaguar—a hitherto unexplored topic in zoo dentistry—and describes its prosthodontic reconstruction.